Reimagining Multiliteracies for Science and Mathematics Teacher Candidates during the Pandemic - Manning-Lewis, Tanya; Sanford, Kathy (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
The researchers used a duo-ethnographic approach to examine mathematics and science teacher-candidates (TCs) experiences with a Multiliteracies Across the Curriculum course during the pandemic and how the shift to online delivery impacted their attitudes. Through one researcher’s course reflections and students’ anonymous course survey comments in 2020, the research revealed that some TCs lack of exposure to literacy-based teaching impacted their literacy identities and initial resistance to the course. However, the shift to online learning, increased course relevance, exposure to diverse online methodologies and multiliterate tools seemed to have positively impacted mathematics and science TCs attitudes toward Multiliteracies Across the Curriculum compared to previous years.